Locus coeruleus lesion & cold stress: Role of the central and peripheral sympathetic nervous system in rat's late proestrous phase - Farideh Zafari Zangeneh; Akram Ahangarpour; Hadi Fathi Moghaddam; Mahnaz kesmati (Tehran University of Medical Sciences, 2010)
Objective: LC/NA system is activator of hypothalamic-pituitar-adrenal (HPA) axis and cold stress triggers an equally robust increase in plasma NA. Increased LHRH content probably due to absence or decrease of NE release from the LC and positive feedback action of E2 on LH secretion show that in late proestrous phase NA, LH and E2 have a strong link. This study was conducted to evaluate the effect of central sympathetic nervous system (by LC lesion and acute cold stress induction) and peripheral sympathetic nervous system (with propranolol administration) on late proestrous phase in rat. Material and Method: One hundred eight rats were divided into control and study groups. Study group was divided into three main sub groups: LC lesion (electrolytic lesion), acute cold stress (4°C for 20 minutes) and propranolol (antagonist of sympathetic nervous system). Vaginal smears were taken for all groups and late proestrous was selective phase for this study. Statistical differences were determined by one-way ANOVA followed by the Tukey post hoc test. SPSS 11 was used for data analysis. P value ≤ 0.05 was defined as significant level. Results: LC lesion decreased only estradiol level (P≤0.001) but could increase serum level of LH like propranolol administration (7mg/kg ip) (P≤0.01). No significant changes were noted in the levels of LH and estradiol in cold stress group like the synergistic effect of LC lesion and Cold stress also synergism of LC lesion, Cold stress and propranolol. Conclusion: This study demonstrated that late proestrous phase has a critical role in LH surge and sympathetic nervous system (NA) and E2 are important and basic factors in this process.